Magnetohydrodynamic equilibria of compressible plasma with mass flow in an axisymmetric tokamak - Cheremnykh, O.K. (Вопросы атомной науки и техники, 2000)
In the present work the problem of ideal MHD equilibria of compressible plasma with mass flow in axisymmetric tokamak is investigated. The generalized Grad-Shafranov equation is derived for an arbitrary coordinate system. Two equations of equilibrium are derived by means of an expansion with respect to the inverse aspect ratio from this equation. It is shown that the Shafranov shift is essentially effected by the toroidal velocity for a conventional tokamak.